2016 IEEE 28th International Conference on Tools With Artificial Intelligence (ICTAI) 2016
DOI: 10.1109/ictai.2016.0015
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Multiagent Framework Based on Online Risk-Aware Planning and Decision-Making

Abstract: A collaborative multiagent framework based on online riskaware planning and decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Additionally, we shall say we have a consensus when the aggregated collective preference imposes a linear order over the objects, and a conflict when there no such linear-selected preference exists. Moreover, we are not considering any consistency or consensus in any linguistic, fuzzy, or social network large-group decision making process during the CRP. Agents are autonomous, have their utility functions, and look for their benefit only, and they are not looking to maximize the complete group social choice function [54][55][56][57]. Otherwise, agents are self-interested, and each one would like to obtain the decision that maximizes its utility [56].…”
Section: Assumptionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, we shall say we have a consensus when the aggregated collective preference imposes a linear order over the objects, and a conflict when there no such linear-selected preference exists. Moreover, we are not considering any consistency or consensus in any linguistic, fuzzy, or social network large-group decision making process during the CRP. Agents are autonomous, have their utility functions, and look for their benefit only, and they are not looking to maximize the complete group social choice function [54][55][56][57]. Otherwise, agents are self-interested, and each one would like to obtain the decision that maximizes its utility [56].…”
Section: Assumptionsmentioning
confidence: 99%
“…. , x n } = {alternatives x i }, n > 0) ranked or ordered by agents or decision makers [2,8,20,23,56,57,59,60,74] (see Figure 3). We found that Arrowś theorem can be represented with the appliance of conflict matrices.…”
Section: Definitions For Voting Proceduresmentioning
confidence: 99%
See 3 more Smart Citations